2008
DOI: 10.1121/1.2934829
|View full text |Cite
|
Sign up to set email alerts
|

Reverberation time measuring methods

Abstract: In this paper different well-established methods of reverberation time measurement are compared. Furthermore, the results obtained using these methods are compared to the results provided by some additional methods which could serve as an in situ tool if, for any reason, the reverberation time measurements cannot be carried out using the standardized methods. The methods compared in this paper include the standardized methods (EN ISO 3382:2000), namely the impulse response measured with pink noise, exponential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The reverberation time has always been the basic indicator of acoustical behavior [12]. In the present work, we measured RT30 (the time in which the sound intensity decreases by 30 dB) as Li and Lam [13].…”
Section: Description and Experimentsmentioning
confidence: 91%
“…The reverberation time has always been the basic indicator of acoustical behavior [12]. In the present work, we measured RT30 (the time in which the sound intensity decreases by 30 dB) as Li and Lam [13].…”
Section: Description and Experimentsmentioning
confidence: 91%
“…In regard to the measurement of acoustic parameters, research by Fausti and Farina [77] revealed differences between RT measurements with a gun and techniques utilizing a dodecahedron speaker especially in the low-frequency range (more than 0.3 s difference in the 125 Hz octave band). A study by Jambrosic et al [76] revealed differences in the measurement of RT between pistol shots of different calibers. In a study by Bradley [92], comparisons between measured values and calculated values (RT, C 80 , C 50 and C 35 ) based on ideal exponential decays showed that such predictions are not particularly accurate but give an indication of the mean trends.…”
Section: Gunshotmentioning
confidence: 99%
“…In regard to the measurement of acoustic parameters, there are several studies where this matter is addressed [68,[75][76][77][78]. A study by Jambrosic et al [76] showed that for measurements of reverberation time (RT) with the use of a balloon, results will deviate in the low-frequency range in rooms, compared with studies using standard techniques (dodecahedron speaker). However, if the measured room is large and reverberant, smaller deviations are to be expected.…”
Section: Balloonmentioning
confidence: 99%
“…As opposed to standardized measurements, the loudspeakers were not omnidirectional. However, it has been shown that the use of sound sources with directional patterns differing from omnidirectional has insignificant influence on reverberation time measurements if the measured room is large and reverberant, and the sound field in the room is diffuse [45]. Moreover, to further compensate the use of non-omnidirectional sound sources, the loudspeakers were directed towards boundary diffusers.…”
Section: Reverberation Roommentioning
confidence: 99%